2010
DOI: 10.1037/a0018333
|View full text |Cite
|
Sign up to set email alerts
|

Delay discounting in current and former marijuana-dependent individuals.

Abstract: Studies have found that a variety of drug dependent groups discount delayed rewards more than matched-controls. This study compared delay discounting for a hypothetical $1000 reward among dependent marijuana users, former dependent marijuana users, and matched-controls. Discounting of marijuana was also assessed in the currently marijuana-dependent group. No significant difference in discounting was detected among the groups, however currently dependent users showed a trend to discount money more than the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
134
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(167 citation statements)
references
References 51 publications
29
134
4
Order By: Relevance
“…Cannabis use was not correlated with discounting in the DD-ST task, a finding consistent with most other published studies (M. W. Johnson et al, 2010;Kollins, 2003). Interestingly, the correlation between cannabis use and DD-MAX AUC remained significant after outliers on the DD-MAX task were removed and participants with high DSM-5 scores for tobacco were excluded from the analysis.…”
Section: Discussionsupporting
confidence: 78%
“…Cannabis use was not correlated with discounting in the DD-ST task, a finding consistent with most other published studies (M. W. Johnson et al, 2010;Kollins, 2003). Interestingly, the correlation between cannabis use and DD-MAX AUC remained significant after outliers on the DD-MAX task were removed and participants with high DSM-5 scores for tobacco were excluded from the analysis.…”
Section: Discussionsupporting
confidence: 78%
“…Behavioral risk taking was greater in adolescents with a mean period of abstinence of 53 days (85) and associated with extent of prior exposure in users with an abstinence period of 25 days (127), but was unaffected in other studies of current users (50,56,125). No delay discounting performance differences were found between current and abstinent users and control subjects (128). Thus, risky decision making and sensitivity to reward are increased during acute intoxication.…”
Section: Decision Making Reward Processing and Delay Discountingmentioning
confidence: 84%
“…Numerous studies have not controlled for premorbid functioning or ascertained current intellectual functioning; .50% of studies did not report IQ or years of education. Where groups were matched on IQ or IQ was controlled for in analyses, persistent impairments to cognition were identified for immediate and delayed memory (79), verbal learning and memory (39,61), verbal fluency, attention, and executive function (61) [although not in other studies (84,128)]. …”
Section: Specificity To Cannabis and Potential Confoundsmentioning
confidence: 99%
“…Numerous studies have found that people often prefer to receive an immediate smaller benefit rather than a delayed larger one (O'Donoghue & Rabin, 1999;Thaler, 1981). Research on individuals suffering from overeating disorders (Rasmussen, Lawyer, & Reilly, 2010) or addictions, including drug (Johnson et al, 2010;Kirby et al, 1999), smoking (Ohmura, Takahashi, & Kitamura, 2005), gambling (Alessi & Petry, 2003) and Internet (Saville, Gisbert, Kopp, & Telesco, 2010) addiction, has shown that they all tend to be more shortsighted than normal, healthy individuals, demonstrating excessive delay discounting rates or small subjective values (MacKillop et al, 2011). These individuals with behavioral abnormalities are more prone to choose immediately available, though smaller benefits over larger, though distant ones (e.g., those that contribute to health or strengthen family and social relationships).…”
mentioning
confidence: 95%